The advance of the farmer - Niemoller, August Fred (My University, 1893)
Introduction: The farmer of a thousand years ago and the farmer of today differ widely. The farmer of that time was considered as belonging to the low and ignorant class, who could not boast of their genealogy as the nobleman were so proud of doing. The nobleman spent their energy in making the farmer subordinate for in this lay their success. An old series of pictures which was reprinted a few years ago well shows the condition of those times. In the first picture was shown the king in his royal robe, the crown upon his head, and the scepter in his hand saying “I rule for all.” Next come the soldier in his military coat, bearing his arms with the words “I fight for all.” Next came the lawyer, “I plea for all” Then came the bishop “I pray for all.” Then there came a long lank half starved farmer taking from his pocket an old wallet “I pay for all.” Yes paying for all, the king in his robes, the soldier in his glistening armor, the bishop in his beautifully decorated church, the lawyer with his stern face, and the farmer paying for all.
Citation: Niemoller, August Fred. The advance of the farmer. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Farmer; Class; Genealogy; Nobleman; Theses; Manuscripts (documents)